A Study of Indonesian Students' Happiness and Its Impact on Chinese L2 Acquisition - Sukma, Sukma (Journal of Maobi, 2024)
This study focuses on exploring the impact of happiness on the learning of Chinese as a second language. The study focuses specifically on students from six universities in Indonesia, providing a targeted sample of learners within a specific context. By examining this particular group of students, the study aims to gain insights into the impact of happiness on Chinese language outcomes among Indonesian learners. In this study include an exploration of the Affective Filter Hypothesis proposed by Stephen Krashen the Affective Filter Hypothesis suggests that learners’ emotional states can act as a filter that ether facilitates or hinder language acquisition. The main research question revolves around whether students’ happiness influences their ability to learn Chinese as a language. The research methodology includes a combination of surveys quantitative and qualitative interviews to gather data. Indonesian students who are studying Chinese as their second language were involved in the study. Surveys were used to assess their perceived progress in learning Chinese and their overall satisfaction levels. Additionally, some participants underwent interviews to delve deeper into their experiences and language learning journey. The findings indicate a correlation between happiness and Chinese language acquisition with levels of happiness associated with increased motivation, reduced anxiety and improved language proficiency. The qualitative analysis revealed that contented students exhibited self-confidence, an attitude towards learning and a willingness to engage with the Chinese language. This study contributes to the broader field of second language acquisition by highlighting the significance of addressing well-being in language learning environments and support the relevance of the Affective Filter Hypothesis. According to the study findings enhancing happiness levels and creating a learning environment will facilitate effective Chinese language acquisition, among Indonesian students. This study calls for further research to explore additional emotional factors and their impact on language acquisition in diverse learner populations.